Controlled co‐immobilization of biomolecules on quinone‐bearing plasma polymer films for multifunctional biomaterial surfaces. Issue 11 (14th June 2020) - Czuba, Urszula; Moreno‐Couranjou, Maryline; Collard, Delphine; De Pauw‐Gillet, Marie‐Claire; Quintana, Robert; Lassaux, Patricia; Detrembleur, Christophe; Choquet, Patrick
Abstract: In this study, an efficient methodology, allowing the controlled co‐immobilization of two complementary biomolecules, is reported for the production of multifunctional antibacterial surfaces. To promote long‐lasting covalent immobilization, metallic surfaces are first coated with a quinone‐bearing poly(methacrylate)‐based thin film by combining an atmospheric pressure liquid‐assisted plasma polymerization and a controlled sodium periodate‐induced catechol oxidation steps. The influence of the oxidation step on the film morphology and chemistry is investigated using an analytical multitool approach involving atomic force microscopy, ultraviolet, infrared, and X‐ray photoelectron spectroscopy techniques. Quartz crystal microbalance with dissipation monitoring (QCM‐D) analyses allow the rapid determination of the optimal biomolecule immobilization conditions in terms of kinetics of grafting and biomolecule solution concentrations. In vitro functional assays combined with QCM‐D analyses demonstrate promising, dual biologically active coated surfaces. Abstract : The atmospheric‐assisted deposition of quinone‐bearing thin films is exploited to control the covalent co‐immobilization of two complementary and biologically active biomolecules for the production of multifunctional biomaterials.